Education and Social Exclusion in India A Policy Perspective - Das, Pankaj (JOURNAL OF INDIAN EDUCATION, 2010)
The estimations of different statistics indicate that a large number of children are out of schooling system in India and majority of these children are from socially disadvantaged and economically deprived communities. A large number of marginalised children including religious minority are not able to access schools and maximum benefits of school opportunities despite the wide expansion of education system across the country. In fact, access to education is strongly and deeply rooted in social attitudes and orientations embedded in social structures and cultural belief systems. These structural and ideological factors play a vital role in producing social inequality and exclusion in education with respect to achievement and participation at all levels. In this context, it is pertinent to examine and analyse the complex relationship between social exclusion and education in a policy perspective for achieving the educational equity.